2014
DOI: 10.1016/j.jash.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early diastolic alterations by Tissue Doppler Imaging in untreated childhood-onset essential hypertension

Abstract: Background Aim of the study was to determine the presence of preclinical diastolic dysfunction in hypertensive children relative to normotensive children by Tissue Doppler Imaging (TDI). Methods We prospectively enrolled children with untreated essential hypertension in absence of any other disease and a matched healthy control group with normal blood pressure (BP); both groups confirmed by clinic BP and a 24 hour ambulatory BP monitoring. Echocardiographic diastolic parameters were determined using spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
3
25
0
1
Order By: Relevance
“…Therefore, it is not surprising that even in children with EH in our study, obesity plays a role in the development of LVH. In our previous study, after multivariate analysis, we demonstrated that LV compliance indices correlated significantly with serum insulin levels in nondiabetic children with EH . Obesity along with elevated triglycerides was seen in association with LVH in our current study, indicating a potential role of cardiometabolic phenotype in the development of LVH among children with EH.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, it is not surprising that even in children with EH in our study, obesity plays a role in the development of LVH. In our previous study, after multivariate analysis, we demonstrated that LV compliance indices correlated significantly with serum insulin levels in nondiabetic children with EH . Obesity along with elevated triglycerides was seen in association with LVH in our current study, indicating a potential role of cardiometabolic phenotype in the development of LVH among children with EH.…”
Section: Discussionsupporting
confidence: 69%
“…Primary hypertension or essential hypertension (EH) can lead to cardiovascular changes in childhood, including subclinical hypertensive cardiomyopathy, aortopathy and vasculopathy . Left ventricular (LV) hypertrophy (LVH), as demonstrated by an increase in LV mass (LVM) on echocardiography, is the most common surrogate marker of end‐organ damage from EH on echocardiography.…”
mentioning
confidence: 99%
“…In another study, 417 patients admitted with heart failure were followed for a median of 306 days [70]; an increase in E/ e' was linearly associated with increased all-cause mortality. E/e' ratio is also useful in detecting early LV DD in patients with untreated early onset hypertension and hyperinsulinaemia [71].…”
Section: E/ E' Ratiomentioning
confidence: 99%
“…Disfungsi diastole terjadi bersamaan dengan fibrosis dan iskemia miokardium pada hipertensi sistemik kronik sehingga disfungsi diastole ventrikel kiri dengan restriksi pengisian ventrikel kiri dianggap sebagai tanda hypertensive heart disease. 18 Penilaian hipertrofi ventrikel kiri dilakukan dengan mengukur ketebalan dinding merupakan faktor sangat penting dalam menilai keparahan disfungsi ventrikel kiri. 16 Indeks massa ventrikel kiri mencerminkan beratnya hipertrofi ventrikel kiri sehingga secara teoritis IMVK mencerminkan tingkat disfungsi diastole.…”
Section: Pembahasanunclassified